Kinematic Analysis of 3-DOF Planer Robot Using Artificial Neural Network - Jolly Atit Shah; S.S. Rattan; Bahadur Chand Nakra (IAES International Journal of Robotics and Automation (IJRA), 2012)
Automatic control of the robotic manipulator involves study of kinematics and dynamics as a major issue. This paper involves the forward and inverse kinematics of 3-DOF robotic manipulator with revolute joints. In this study the Denavit- Hartenberg (D-H) model is used to model robot links and joints. Also forward and inverse kinematics solution has been achieved using Artificial Neural Networks for 3-DOF robotic manipulator. It shows that by using artificial neural network the solution we get is faster, acceptable and has zero error.DOI: http://dx.doi.org/10.11591/ijra.v1i3.511